The USE OF GOOGLE TRANSLATE IN ENHANCING EFL STUDENTS' WRITING SKILL - Hasan Rizky, Fauzan; Martriwati (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
This study investigates the impact of Google Translate (GT), an AI-powered translation tool, on the writing skills of EFL (English as a Foreign Language) high school students in Jakarta, Indonesia. Employing a mixed-methods approach, the research includes quantitative data from 200 students via a Likert-scale questionnaire and qualitative data from semi-structured interviews with 10 students. The findings reveal that students generally perceive GT as helpful, especially for vocabulary acquisition and comprehension. However, there is a negative correlation between students’ writing performance and their reliance on GT. Overuse of GT may hinder critical thinking and reduce students’ independent writing skills. Furthermore, some students demonstrate strategies to reduce dependence on GT and engage in self-learning through traditional dictionaries, media exposure, and reading. Teachers also emphasize the need for guided use of GT. The study concludes that GT can support EFL learning if it is integrated carefully, complementing rather than replacing independent language practice.